A star-wheeled sky - Torgersen, Brad R. (Baen Publishing Enterprises, 2020)
"THE WAYPOINT TO ULTIMATE POWER! Over a millennium in the past, humans fleeing Earth in slower-than-light vessels discovered the Waywork, an abandoned alien superhighway system that allows instantaneous travel from star to star. The problem: there are a finite number of Waypoint nodes-and the burgeoning population of humans is hemmed in as a result. Furthermore, humanity is divided into contending Starstates. One of the strongest is based on an oligarchy ruling families, but still mostly democratic. The other is a totalitarian nightmare. War seems inevitable. Now a new Waypoint appears. Might it lead to the long-lost creators of the Waywork? If so, there may be knowledge and technology that will tip the balance in the coming war. Three people race to make it to the new Waypoint-and beyond. These include Wyodreth Antagean, the reluctant son of an interstellar shipping magnate, Lady Garsina Oswight, the daring daughter of a royal family, and Zuri Mikton, a disgraced flag officer seeking redemption. They are facing an implacable foe in Golsubril Vex, a merciless, but highly effective, autocrat from the Waywork's most brutal regime. Vex is determined to control the new Waypoint and whatever revelation or power lies on the other side. Now humanity's fate-to live in freedom or endless dictatorship-depends on just what that revelation might be. And who gets there first"--